Mandibular distraction in neonates: indications, technique, results - Sesenna Enrico; Magri Alice S; Magnani Cinzia; Brevi Bruno C; Anghinoni Marilena L (BMC, 2012)
Abstract Background The Pierre Robin Sequence features were first described by Robin in 1923 and include micrognathia, glossoptosis and respiratory distress with an incidence estimated as 1:8,500 to 1:20,000 newborns. Upper airway obstruction and feeding difficulties are the main concerns related to the pathology. Mandibular distraction should be considered a treatment option (when other treatments result inadequate). Patiants and methods Ten patients between the ages of 1 month and 2 years with severe micrognathia and airway obstruction were treated with Mandibular Distraction Osteogenesis (MDO). All patients underwent fibroscopic examination of the upper airway and a radiographic imaging and/or computed tomography scans to detect malformations and to confirm that the obstruction was caused by posterior tongue displacement. All patients were evaluated by a multidisciplinary team. Indications for surgery included frequent apneic episodes with severe desaturation (70%). Gavage therapy was employed in all patients since oral feeding was not possible. The two tracheotomy patients were 5 months and 2 years old respectively, and the distraction procedure was performed to remove the tracheotomy tube. All patients were treated with bilateral mandibular distraction: two cases with an external multivector distraction device, six cases with an internal non-resorbable device and two cases with an internal resorbable device. In one case, the patient with Goldenhar's Syndrome, the procedure was repeated. Results The resolution of symptoms was obtained in all patients, and, when present, tracheotomy was removed without complications. Of the two patients with pre-existing tracheotomies, in the younger patient (5 months old) the tracheotomy was removed 7 days postoperatively. In the Goldenhar's syndrome case (2 years old) a Montgomery device was necessary for 6 months due to the presence of tracheotomy-inducted tracheomalacia. Patients were discharged when the endpoint was obtained: symptoms and signs of airway obstruction were resolved, PAS and maxillomandibular relationship improved, and tracheotomy, when present, removed. During the follow-up, no injury to the inferior alveolar nerve was noted and scarring was significant in only the two cases treated with external devices. Conclusion Mandibular Distraction Osteogenesis is a good solution in solving respiratory distress when other procedures are failed in paediatric patients with severe micrognatia.